2016
DOI: 10.1155/2016/6957101
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Bilateral 3-4 Metatarsal Syndactyly in a Pet Rabbit

Abstract: We report the first case of spontaneous syndactyly reported in a pet rabbit. Syndactyly only caused an atypical gait in the rabbit. The radiological study revealed bilateral 3rd and 4th metatarsal bones fused in its entire length preserving normal joint surfaces resembling syndactyly type Ia. The cause of this congenital malformation was unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies identified E. cuniculi by PCR in an AIDS patient (genotype III) [ 35 ], Crohn’s disease patients [ 39 ], water samples from Madrid (genotypes I and III) [ 38 ], the Iberian lynx ( Lynx pardinus ) in southern Spain [ 40 ], and captive chimpanzees ( Pan troglodytes ) in Madrid (genotype I) [ 41 ], demonstrating the presence of this species in mainland Spain. Furthermore, other studies reported cases in domestic rabbits in Spain using indirect immunofluorescence testing [ 36 ], histopathological analysis [ 42 , 43 ], or serological analysis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. However, the molecular characterization of E. cuniculi in rabbits from Spain has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified E. cuniculi by PCR in an AIDS patient (genotype III) [ 35 ], Crohn’s disease patients [ 39 ], water samples from Madrid (genotypes I and III) [ 38 ], the Iberian lynx ( Lynx pardinus ) in southern Spain [ 40 ], and captive chimpanzees ( Pan troglodytes ) in Madrid (genotype I) [ 41 ], demonstrating the presence of this species in mainland Spain. Furthermore, other studies reported cases in domestic rabbits in Spain using indirect immunofluorescence testing [ 36 ], histopathological analysis [ 42 , 43 ], or serological analysis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. However, the molecular characterization of E. cuniculi in rabbits from Spain has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%